Phenomenological model for the interpretation of impedance/admittance spectroscopy results in polymer light-emitting electrochemical cells - Gozzi, G. [UNESP]; Cagnani, L. D.; Faria, R. M.; Santos, L. F. [UNESP] (Springer, 2014)
A phenomenological model has been developed to account for the results of impedance/admittance spectroscopy measurements from light-emitting electrochemical cells (LECs) comprising a polymer electrolyte and two different conjugated polymers used as organic semiconductor. The application of a d.c. offset bias superimposed to the a.c. modulation voltage was used to observe the transition from the behavior prior to device operation and after the formation of the electrochemical p-i-n junction. The analysis of the whole device "conductivity" as a function of the applied bias and of the frequency was used to support the assumptions considered to develop the model. The results show that the device, after the p-i-n junction formation, can be considered as composed by two highly conductive electrochemically doped (n and p) regions and a thin (few tens nanometers), insulating layer, where the electrical current is dominated by electronic charge carrier injection via tunneling through a rectangular energy barrier. Before the p-i-n junction formation, there is no doping of semiconductor material, and the device electrical properties are dominated by the intrinsic electronic charge carriers in the organic semiconductor. Results from devices made of organic semiconductors with different band gap energy and different layer thicknesses are used to corroborate the proposed model.
Keywords: Light-emitting electrochemical cells; Impedance/admittance spectroscopy; Organic electronics